A Rare and Clinically Important Blood Group - Bombay Blood Group - Chowdhury, FS; Siddiqui, MAE; Rahman, KGM; Nasreen, Z; Begum, HA; Begum, HA (Bangladesh Journal of Medicine, 2013)
Bombay blood group is the rarest blood group in the world. It is a blood group which shows absence of A,B,H antigens on red cells and presence of anti- A, anti-B and potent wide thermal range anti-H antibodies in serum reacting with all O blood group. Dr. Y.M. Bhende first discovered Bombay blood group in 1952 at Bombay in India now known as Mumbai. This is the reason why this blood group got the name Bombay blood group. DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13596 Bangladesh J Medicine 2011; 22: 21-23